Challenges for The Ferry Shipping Operation in The Baltic Sea Region in The Time of COVID-19 Pandemic - Ilona URBANYI-POPIOŁEK (Communications of International Proceedings, 2020)
Ferry shipping is a type of maritime transportation where passengers and cargo are transported in one ship and form one market. The demand for transportation is created by two segments – people travelling in different purposes and hauliers transported cargo in trailers. Baltic Sea constitutes the prime area of ferry operation in Europe. The network of international and prime domestic ferry connections included 60 services with 116 ferries operated (ro-pax, cruise-roro i high-speed). As the ferry business is concentrated, the operations are provided by 16 main ferry operators. On international and main domestic ferry lines the traffic amounted to around 49 million passengers, 9 million cars and 3 million trailers. In previous decades changes in internal factors determining operation were to a certain extent predictable. COVID-19 epidemic started unexpectedly and created new challenges for shipowners they have to face. The latter factor suddenly hit the ferry business. The purpose of the paper is to research into the ferry operation in the time of pandemic and evaluate the activities of the operators to reduce the negative effects in turnover decline. The paper begins with introduction (Section 1) and methodology (Section 2). The main body comprises the theoretical background of ferry shipping and presentation of the Baltic ferry operation, as well as discussed, the management of operation in time of pandemic. The methods used in this study are the analyses of literature, analyses of original data and in-depth interviews.
Keywords: Ferry Operation; Baltic Sea; COVID-19; Ferry Carriers; Cargo Transportation; Ferry Tourism.